Otimização multiobjetivo aplicada aos motores de indução validada via elementos finitos - Malagoli, Juliana Almansa (2016)
The design of engineering systems is configured as a multiobjective problem. This in turn is inherently conflicting, that is, the improvement in one of the objectives results in worsening the other. Among the numerous applications that can be found in the literature, the design of three-phase induction motor, basis functions whose alternating currents are induced in the rotor circuit, rotating magnetic field produced by the stator coils, appears as an interesting research topic, since it is directly related to manufacturing costs of motors. In this context, this thesis aims the multiobjective optimization of electrical machines via finite elements considering, for example, as objectives minimizing the volume of the machine and maximizing energy efficiency via determining the vector of geometric variables that characterize the mathematical model presented. For this purpose are used multiobjective differential evolution algorithm and the results obtained are compared with those obtained by multiobjective genetic algorithm. The results preliminary indicate that the proposed methodology configures as an interesting alternative for the purpose described above.